Effectiveness of an Instructional program on patients with ulcerative colitis adherence for Medication and Diet to prevent Colorectal Cancer: case and control study - fauze, faris (Iraqi National Journal of Nursing Specialties, 2022)
ABSTRACT:Objectives: The study aims to know the effectiveness of the educational program in the patient’s adherence to medication and diet and to know the relationship between the effectiveness of the education program and their demographic data related to the patient’s age, gender, marital status, education level, occupation, monthly income and residence.Methodology: A quasi -experimental design study was performed on patient who attended to Gastroenterology and Hepatology Teaching Hospital, from March 2021 to September 2021. The non-probability sampling including 50 patients for case study and 30 patients for control group. The questionnaire consists of 3 parts, part one the socio-demographic consist of 8 items. Part two    consist of 12 items related to patient adherence for medications. Part three dealing the adherence of patient for diet which include 14 items. Results: the study's findings revealed that 45.7% of case group was adherence with healthy diet at pretest while the percent of their adherence was improved to 62.4% at posttest, their adherence for medication was 42.2% at pretest, and their adherence for medication was improved to 78.3% at posttest.Conclusion: The study concluded that was effective on case group patientsOn their adherence for healthy diet and medication to avoid colorectal cancerRecommendations: The study recommends increase the patient’s health awareness toward the complication of ulcerative colitis, and establishing rehabilitation units in hospitals for guiding the patient about the importance of adhering to a balanced diet and treatment.